KONTRIBUSI WANITA DALAM AKTIVITAS EKONOMI DAN RUMAH TANGGA KABUPATEN MALANG - Waluyo, Dwi Eko; Yuliati, Uci (Faculty of Economics and Business, University of Muhammadiyah Malang, 2015)
This study was conducted to discover the women contribution on the dynamics of village economic activities. It was a very interesting topic to discuss since most of women in the village have low educational background and always directed to be workers. The respondents of this project were 51 housemaids who were selected by employing purposive sampling technique. Subsequently, the data which consisted of variables in the form of individual characteristics, earnings, and working hours were analyzed using cross-tabulation. The results showed that the majority of women workers' education is elementary school (47.1%), junior high school (37.3%), senior high school (7.8%) and they were mostly less than 45 years old. In conclusion, women's income had contributed well to meet the expectations of family economy with average wage was 350,000 rupiah per month for 8 work hours per day.